Thermotolerance of tomato plants grafted onto wild relative rootstocks - Lee, Chungkeun; Harvey, Joshua T.; Nagila, Asmita; Qin, Kuan; Leskovar, Daniel I. (Frontiers in Plant Science, 2023)
Heat stress is a major environmental constraint limiting tomato production. Tomato wild relatives Solanum pennellii and S. peruvianum are known for their drought tolerance but their heat stress responses have been less investigated, especially when used as rootstocks for grafting. This study aimed to evaluate the physiological and biochemical heat stress responses of tomato seedlings grafted onto a commercial 'Maxifort' and wild relative S. pennellii and S. peruvianum rootstocks. 'Celebrity' and 'Arkansas Traveler' tomato scion cultivars, previously characterized as heat-tolerant and heatsensitive, respectively, were grafted onto the rootstocks or self-grafted as controls. Grafted seedlings were transplanted into 10-cm pots and placed in growth chambers set at high (38/30 °C, day/night) and optimal (26/19 °C) temperatures for 21 days during the vegetative stage. Under heat stress, S. peruvianum-grafted tomato seedlings had an increased leaf proline content and total non-enzymatic antioxidant capacity in both leaves and roots. Additionally, S. peruvianum-grafted plants showed more heat-tolerant responses, evidenced by their increase in multiple leaf antioxidant enzyme activities (superoxide dismutase, catalase and peroxidase) compared to self-grafted and 'Maxifort'grafted plants. S. pennellii-grafted plants had similar or higher activities in all antioxidant enzymes than other treatments at optimal temperature conditions but significantly lower activities under heat stress conditions, an indication of heat sensitivity. Both S. pennellii and S. peruvianum-grafted plants had higher leaf chlorophyll content, chlorophyll fluorescence and net photosynthetic rate under heat stress, while their plant growth was significantly lower than self-grafted and 'Maxifort'-grafted plants possibly from graft incompatibility. Root abscisic acid (ABA) content was higher in 'Maxifort' and S. peruvianum rootstocks, but no ABA-induced antioxidant activities were detected in either leaves or roots. In conclusion, the wild relative rootstock S. peruvianum was effective in enhancing the thermotolerance of scion tomato seedlings, showing potential as a breeding material for the introgression of heat-tolerant traits in interspecific tomato rootstocks.